2014
DOI: 10.1109/jstars.2014.2332872
|View full text |Cite
|
Sign up to set email alerts
|

Crevasse Detection in Ice Sheets Using Ground Penetrating Radar and Machine Learning

Abstract: This paper presents methods to automatically classify ground penetrating radar (GPR) images of crevasses on ice sheets. We use a combination of support vector machines (SVMs) and hidden Markov models (HMMs) with down sampling, a preprocessing step that is unbiased and suitable for real-time analysis and detection. We perform modified crossvalidation experiments with 129 examples of Greenland GPR imagery from 2012, collected by a lightweight robot towing a GPR. In order to minimize false positives, an HMM class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…However, ground penetrating radar (GPR), a non-destructive technique, can be used to collect both point as well as spatial distribution of snow thickness. It has been widely used in ground mode, for snow and ice thickness measurements [8][9][10][11][12][13][14][15] , snowpack stratigraphic delineation 16 and to study the subsurface properties of other strata 17 . Forte et al 18,19 reported the applications of GPR data in determining the density and electromagnetic (EM) wave velocity for snow, firn and ice.…”
mentioning
confidence: 99%
“…However, ground penetrating radar (GPR), a non-destructive technique, can be used to collect both point as well as spatial distribution of snow thickness. It has been widely used in ground mode, for snow and ice thickness measurements [8][9][10][11][12][13][14][15] , snowpack stratigraphic delineation 16 and to study the subsurface properties of other strata 17 . Forte et al 18,19 reported the applications of GPR data in determining the density and electromagnetic (EM) wave velocity for snow, firn and ice.…”
mentioning
confidence: 99%
“…Many studies were performed on detecting different type of anomalies: mine detection ( [5][6][7][8]) sinkholes [9], subterranean voids and tunnel detection [10,11], buried utilities [12] cracks in ice sheets [13]) as well as for bridges and roads assessment [14]. The vast majority of detection methods involve some pre-processing stage (for example: Qin et Al.…”
Section: Related Workmentioning
confidence: 99%
“…Such study is important to assess the factors controlling the development of debris flows and to identify the areas susceptible to their occurrences. In [24], methods are presented to automatically classify GPR images of crevasses on ice sheets using a combination of SVMs and hidden Markov models (HMMs). The combined HMM-SVM method retains all of the correct classifications by the SVM, reduces the false positive rate, and also reduces the computational burden in classifying GPR traces.…”
Section: E Natural and Manmade Disaster Related Applicationsmentioning
confidence: 99%